Preparation method of organic flame retardant and application of organic flame retardant in PVC black master batch

Through a new organic flame retardant preparation method, combined with organic and inorganic flame retardant, the shortcomings of PVC color masterbatch in flame retardant and smoke suppression performance are solved, and the excellent flame retardant and smoke suppression effect of PVC black masterbatch is achieved.

CN119708633APending Publication Date: 2025-03-28VULCHEM MATERIALS TECH (CHANGSHU) CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510227635.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing PVC masterbatch has shortcomings in flame retardant effects, especially the poor performance of suppressing the generation of toxic smoke, which makes it difficult to meet the flame retardant and smoke suppression needs of PVC materials.

Method used

A new organic flame retardant preparation method is adopted to produce product a by reaction of the flame retardant DOPO and the benzylquinone, and the product b with excellent flame retardant properties is generated by reaction of the hydroxyl group on the product a with isocyanate propyltriethoxysilane. This method combines organic and inorganic coordinated flame retardant to improve the dispersion of flame retardant in polymer matrix.

Benefits of technology

It realizes excellent flame retardant and smoke suppression performance of PVC black masterbatch, can effectively suppress the generation of toxic smoke, and significantly improves the safety and reliability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention belongs to the technical field of organic flame retardants and macromolecular color master batches, and particularly relates to a preparation method of an organic flame retardant and application of the organic flame retardant in PVC black master batches. The preparation method comprises the following steps: 1) preparing a product a; 2) preparing a product b; and 3) preparing the organic flame retardant. The invention has the following beneficial effects: 1) a flame retardant DOPO is selected to react with p-benzoquinone to prepare a product a, hydroxyl on the product a reacts with isocyanate group on isocyanate propyl triethoxy silane to generate a product b, and the product b is a silicon-phosphorus compound, contains siloxy and has excellent flame retardant property; and 2) firstly preparing a flame-retardant and smoke-suppressing hybrid matrix, reacting hydroxyl on the hybrid matrix with an isocyanate group, grafting isocyanate propyl triethoxy silane to the hybrid matrix, introducing a silicon-oxygen bond, then blending with a product b for hydrolysis, hydrolyzing the silicon-oxygen bond into hydroxyl for condensation, and grafting the product b to the hybrid matrix to form the organic flame retardant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of organic flame retardants and polymer color masterbatches, and particularly relates to a preparation method of an organic flame retardant and application of the organic flame retardant in PVC black masterbatches. Background Art

[0002] Most polymer materials, such as general-purpose polyethylene (PE), polyvinyl chloride (PVC), polypropylene (PP), polystyrene (PS), etc., are flammable or combustible.

[0003] Masterbatch is a plastic colorant made by well dispersing a high proportion of pigments or additives with thermoplastic resins. The selected resin has good wetting and dispersing effects on the colorant, good compatibility with the colored material, and good affinity for the pigment.

[0004] Patent application CN107118470 A discloses an environmentally friendly PVC black masterbatch, whose components are: 100-120 parts of polyvinyl fluoride; 2-30 parts of carbon black; 3-8 parts of polyethylene low molecular weight wax; 3-8 parts of stearate; 0.5-3 parts of heat stabilizer. It solves the technical problems of color instability and uncontrollable color difference caused by poor thermal stability of existing masterbatches, but it does not involve flame retardant effect. In particular, for PVC materials, smoke suppression effect is more important than flame retardancy, but this patent does not involve this.

[0005] Therefore, how to develop a PVC masterbatch with a wide range of applications, good flame retardant effect, and the ability to suppress the generation of toxic smoke is a technical problem that needs to be solved urgently. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a preparation method of an organic flame retardant and application of the organic flame retardant in PVC black masterbatch.

[0007] The technical solution adopted to achieve one purpose of the present invention is: A method for preparing an organic flame retardant comprises the following steps: Step 1): Preparation of product a: adding flame retardant DOPO to tetrahydrofuran, heating and stirring until dissolved, adding p-benzoquinone, and conducting microwave heating reaction. After the reaction is completed, cooling to room temperature, suction filtering, washing with tetrahydrofuran to obtain a crude product, vacuum drying, recrystallizing with tetrahydrofuran, and drying to obtain product a; Step 2): Preparation of product b: Add product a obtained in step 1) into tetrahydrofuran, and sequentially add isocyanate propyltriethoxysilane and n-butyltin dilaurate, introduce nitrogen gas for reflux reaction, and obtain product b; Step 3): Preparation of organic flame retardant: Add the hybrid matrix, isocyanate propyl triethoxysilane and n-butyltin dilaurate into tetrahydrofuran, heat up, introduce nitrogen for reflux reaction, add the product b obtained in step 2) after the reaction is completed, add deionized water and hydrochloric acid solution, keep warm and stir evenly, add ammonia water, continue stirring and react, and then rotary evaporate to obtain a crude product, add it into anhydrous ethanol, filter, wash, and vacuum dry to obtain an organic flame retardant.

[0008] Preferably, in step 1), the amount ratio of the flame retardant DOPO, tetrahydrofuran and p-benzoquinone is 100g: (300-500)mL: 50g; the microwave heating reaction has a heating temperature of 50-55°C, a microwave power of 300-500W, and a reaction time of 3-5min.

[0009] Preferably, in step 2), the usage ratio of the product a, isocyanatepropyltriethoxysilane, n-butyltin dilaurate and tetrahydrofuran is (7.2-7.5) g: 6.5 g: (0.1-0.2) g: 100 mL.

[0010] Preferably, in step 3), the amount ratio of the hybrid matrix, isocyanatepropyltriethoxysilane, n-butyltin dilaurate, tetrahydrofuran, product b, deionized water, hydrochloric acid solution and ammonia water is (5-6) g: 1 g: (0.1-0.2) g: (100-300) mL: 5 g: (10-100) mL: (1-5) mL: (1-5) mL; the heating temperature is 55-65° C., and the reflux reaction time is 3-6 h; the concentration of the hydrochloric acid solution is 0.5-1 mol / L; and the mass percentage of the ammonia water is 25-30%.

[0011] More preferably, the hybrid matrix of the present invention is prepared by the following steps: Step 1): Add magnesium chloride, aluminum chloride and rhenium chloride into deionized water, stir evenly after heating, add mixed alkali solution to adjust pH, heat and react after aging, filter after the reaction, wash the filter cake with anhydrous ethanol and deionized water until the washing liquid is neutral, then vacuum dry and grind to obtain rhenium ion-doped magnesium aluminum hydrotalcite powder, and prepare rhenium ion-doped magnesium aluminum hydrotalcite powder dispersion; Step 2): Add n-hexane to n-butyl lithium solution, add molybdenum disulfide, heat and then carry out heat preservation reaction, filter, wash the filter cake with n-hexane to obtain product c, add product c to deionized water, ultrasonically strip and add to rhenium ion-doped magnesium aluminum hydrotalcite powder dispersion, stir at a uniform speed at room temperature, filter after stirring, wash the filter cake with anhydrous ethanol, vacuum dry, grind, and obtain a hybrid matrix.

[0012] More preferably, the molar ratio of magnesium chloride, aluminum chloride and rhenium chloride in the present invention is 10:5:(1-2); the mixed alkali solution is prepared by the following steps: a sodium carbonate solution with a concentration of 3 g / mL and a sodium hydroxide solution with a concentration of 5 g / mL are stirred evenly in a volume ratio of 1:1 to prepare a mixed alkali solution; the rhenium ion-doped magnesium-aluminum hydrotalcite powder dispersion is prepared by the following steps: rhenium ion-doped magnesium-aluminum hydrotalcite powder and deionized water are mixed in a mass volume ratio of 1 g:1000 mL.

[0013] More preferably, the dosage ratio of n-hexane, n-butyl lithium solution and molybdenum disulfide in the present invention is (30-35) mL: 10 mL: (1.5-3) g, and the dosage ratio of the product c, deionized water and rhenium ion-doped magnesium aluminum hydrotalcite powder dispersion is 1 g: 1000 mL: (500-1000) mL.

[0014] The technical solution adopted to achieve another purpose of the present invention is: The invention discloses an application of an organic flame retardant in a PVC black masterbatch. The PVC black masterbatch comprises, by weight, 10 to 25 parts of an organic flame retardant, 30 to 50 parts of a carrier, 70 to 90 parts of carbon black, 5 to 10 parts of a dispersant and 2 to 5 parts of talc.

[0015] Preferably, the PVC black masterbatch of the present invention is prepared by the following method: grinding and sieving carbon black for use, adding a carrier into a mixer, heating to 190-200° C. and mixing for 1-2 hours, then adding a dispersant, continuing to mix for 30-45 minutes, then adding carbon black, talcum powder and an organic flame retardant, and continuing to mix for 1-3 hours to obtain a black masterbatch.

[0016] More preferably, the carrier of the present invention is one or more of styrene-butadiene-acrylonitrile copolymer, polystyrene and styrene-butadiene copolymer mixed in any proportion, and the dispersant is polyethylene wax or metal stearate.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The present invention proposes a new method for preparing an organic flame retardant. The flame retardant DOPO is selected to react with p-benzoquinone to prepare a product a. The hydroxyl group on the product a reacts with the isocyanate group on isocyanatepropyltriethoxysilane to generate a product b, which is a silicon-phosphorus compound containing a silicon radical and has excellent flame retardant properties.

[0018] The present invention first prepares a flame retardant and smoke suppressing hybrid matrix, and connects isocyanate propyl triethoxysilane to the hybrid matrix through the reaction of hydroxyl groups on the hybrid matrix to introduce silicon-oxygen bonds, and then mixes and hydrolyzes it with product b, the silicon-oxygen bonds are hydrolyzed into hydroxyl groups for condensation, and the product b is connected to the hybrid matrix to form an organic flame retardant.

[0019] The invention realizes organic / inorganic synergistic flame retardancy, and the introduced organic compound can improve the dispersibility of the flame retardant in the polymer matrix.

[0020] The PVC black masterbatch of the invention uses a carrier resin as a matrix, adds carbon black to prepare a black masterbatch, and adds an organic flame retardant to provide the black masterbatch with excellent flame retardant and smoke suppression performance. DETAILED DESCRIPTION

[0021] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] The present invention provides a method for preparing an organic flame retardant, which comprises the following preparation steps: Step 1): Preparation of product a: add commercially available flame retardant DOPO to tetrahydrofuran, heat and stir until dissolved, add p-benzoquinone, then transfer to a microwave oven for microwave heating reaction, cool to room temperature after the reaction is completed, filter, wash with ice-crystallized tetrahydrofuran to obtain a crude product, vacuum dry, recrystallize with tetrahydrofuran, and dry to obtain product a; In step 1), the flame retardant DOPO reacts with p-benzoquinone to prepare product a, the structural formula of which is shown below: ; Step 2): Preparation of product b: Add product a to tetrahydrofuran, add isocyanatepropyltriethoxysilane and n-butyltin dilaurate in sequence, introduce nitrogen gas for reflux reaction, and obtain product b; In step 2), under the conditions of tetrahydrofuran as solvent and n-butyltin dilaurate as catalyst, the hydroxyl group on product a reacts with the isocyanate group on isocyanatepropyltriethoxysilane to generate product b, which is a silicon-phosphorus compound containing siloxy groups and has excellent flame retardant properties.

[0023] Step 3): Preparation of organic flame retardant: adding a hybrid matrix, isocyanate propyl triethoxysilane and n-butyltin dilaurate to tetrahydrofuran, heating, introducing nitrogen gas for reflux reaction, adding product b obtained in step 2) after the reaction, adding deionized water and hydrochloric acid solution, keeping warm and stirring at a constant speed, adding ammonia water and continuing stirring reaction, then rotary evaporation to remove the solvent to obtain a crude product, adding it to anhydrous ethanol, suction filtering, washing, and vacuum drying to obtain an organic flame retardant; The present invention firstly reacts the hydroxyl group on the hybrid matrix with the isocyanate group, connects isocyanate propyl triethoxysilane to the hybrid matrix, introduces silicon-oxygen bonds, and then hydrolyzes the silicon-oxygen bonds to form hydroxyl condensation, connects the product b to the hybrid matrix, forms a multi-element flame retardant, realizes organic / inorganic synergistic flame retardancy, and gives the finally prepared organic flame retardant an excellent flame retardant effect. In addition, the introduced organic compound can improve the dispersibility of the flame retardant in the polymer matrix.

[0024] Further: the hybrid matrix is ​​prepared by the following steps: Step 1): Add magnesium chloride, aluminum chloride and rhenium chloride into deionized water, stir evenly after heating, add mixed alkali solution to adjust pH, heat and react after aging, filter and wash the filter cake with anhydrous ethanol and deionized water until the washing liquid is neutral, then vacuum dry and grind to obtain rhenium ion-doped magnesium aluminum hydrotalcite powder, and prepare rhenium ion-doped magnesium aluminum hydrotalcite powder dispersion; In step 1), rhenium ion-doped magnesium aluminum hydrotalcite powder is prepared by a hydrothermal method assisted co-precipitation method; Step 2): n-hexane is added to n-butyl lithium solution, molybdenum disulfide is added, the temperature is raised and then the reaction is carried out by heat preservation, filtering, and the filter cake is washed with n-hexane to obtain product c, and product c is added to deionized water, ultrasonically stripped, and rhenium ion-doped magnesium aluminum hydrotalcite powder dispersion is added, and stirred at a uniform speed at room temperature. After the stirring is completed, suction is filtered, and the filter cake is washed with anhydrous ethanol, vacuum dried, and ground to obtain a hybrid matrix; In step 2), n-butyl lithium is used as a strong reducing agent to embed lithium ions into layered molybdenum disulfide, and then ultrasonically peeled off to form a flaky structure to obtain a product, which is a negatively charged flaky lithium-embedded molybdenum disulfide nanosheet. Then, the flaky lithium-embedded molybdenum disulfide nanosheet and the rhenium ion-doped magnesium aluminum hydrotalcite powder dispersion are hybridized by strong electrostatic action to obtain a hybrid matrix. Adding the hybrid matrix to a polymer material matrix (such as plastic) can increase the carbon yield during combustion and form an expanded carbon layer. The expanded carbon layer can protect the underlying polymer and inhibit thermal oxygen exchange. The barrier effect of the molybdenum disulfide nanosheet itself in the hybrid matrix can isolate thermal oxygen exchange and inhibit the penetration of volatile degradation products. The degradation of the doped hydrotalcite can produce porous metal oxides on the surface of the carbon layer, inhibit the combustion of the plastic matrix and absorb the generated smoke. The hybrid matrix has excellent flame retardant and smoke suppression effects through synergistic flame retardancy.

[0025] A method for preparing a PVC black masterbatch comprises the following steps: The carbon black is ground and sieved for later use; the carrier is added into a mixer, the temperature is raised to 190-200°C and the mixer is mixed for 1-2 hours, then a dispersant is added, and after mixing for 30-45 minutes, carbon black, talcum powder and an organic flame retardant are added, and the black masterbatch is obtained after mixing for 1-3 hours.

[0026] Furthermore: the carrier is one or more of styrene-butadiene-acrylonitrile copolymer, polystyrene and styrene-butadiene copolymer mixed in any proportion, and the dispersant is polyethylene wax or metal stearate. Example 1

[0027] An organic flame retardant is prepared by the following steps: 1) Preparation of hybrid matrix Add magnesium chloride, aluminum chloride and rhenium chloride into deionized water, heat to 75°C, stir at a speed of 500r / min for 1h, add mixed alkali solution to adjust pH until pH=11, age for 4h, then heat to 100°C, keep warm for 12h, filter after the reaction, wash the filter cake with anhydrous ethanol and deionized water until the washing liquid is neutral, then vacuum dry for 12h, grind to obtain rhenium ion-doped magnesium aluminum hydrotalcite powder, and control the molar ratio of magnesium chloride, aluminum chloride and rhenium chloride to be 10:5:1; finally prepare rhenium ion-doped magnesium aluminum hydrotalcite powder dispersion: mix rhenium ion-doped magnesium aluminum hydrotalcite powder and deionized water at a mass volume ratio of 1g:1000mL; The mixed alkali solution is prepared by the following steps: a sodium carbonate solution with a concentration of 3 g / mL and a sodium hydroxide solution with a concentration of 5 g / mL are uniformly stirred in a volume ratio of 1:1 to prepare a mixed alkali solution; Add n-hexane to a 2.5 mol / L n-butyl lithium solution, add molybdenum disulfide, heat to 90°C, keep warm for 4 hours, filter, wash the filter cake with n-hexane to obtain product c, add product c to deionized water, ultrasonically peel for 4 hours, add rhenium ion-doped magnesium aluminum hydrotalcite powder dispersion, stir at room temperature for 10 hours, filter after stirring, wash the filter cake with anhydrous ethanol, vacuum dry at 75°C for 10 hours, grind to obtain a hybrid matrix; control the dosage ratio of n-hexane, n-butyl lithium solution and molybdenum disulfide to 30mL:10mL:1.5g, and the dosage ratio of product c, deionized water and rhenium ion-doped magnesium aluminum hydrotalcite powder dispersion to 1g:1000mL:1000mL; 2) Preparation of product a The commercially available flame retardant DOPO (Jiangyin Hanfeng Technology Co., Ltd.) was added to tetrahydrofuran, heated and stirred until dissolved, and p-benzoquinone was added, and then transferred to a microwave oven, heated to 50°C, and the microwave radiation power was controlled to 300W, and the radiation time was 5min. The product was cooled to room temperature, filtered, and washed three times with frozen tetrahydrofuran to obtain a crude product, which was vacuum dried for 10h, and then recrystallized with tetrahydrofuran and dried to obtain product a; the amount ratio of flame retardant DOPO, tetrahydrofuran and p-benzoquinone was controlled to be 100g:300mL:50g; 3) Preparation of product b Add product a to tetrahydrofuran, add isocyanate propyl triethoxysilane and n-butyltin dilauric acid in sequence, introduce nitrogen and reflux for 12 hours to obtain product b; control the amount ratio of product a, isocyanate propyl triethoxysilane, n-butyltin dilauric acid and tetrahydrofuran to 7.2g:6.5g:0.1g:100mL; 4) Preparation of organic flame retardants The prepared hybrid matrix, isocyanate propyl triethoxysilane and n-butyltin dilaurate are added to tetrahydrofuran, the temperature is raised to 60°C, nitrogen is introduced and refluxed for 6 hours, and after the reaction is completed, product b is added, deionized water and a hydrochloric acid solution with a concentration of 0.5 mol / L are added, and the mixture is kept warm and stirred at a constant speed for 2 hours, and then 25% by weight of ammonia water is added, and stirring is continued for 2 hours. The solvent is then removed by rotary evaporation to obtain a crude product, which is added to anhydrous ethanol, filtered, washed, and vacuum dried for 12 hours to obtain an organic flame retardant. The amount ratio of the hybrid matrix, isocyanate propyl triethoxysilane, n-butyltin dilaurate, tetrahydrofuran, product b, deionized water, hydrochloric acid and ammonia water is controlled to be 5g:1g:0.1g:100mL:5g:10mL:1mL:1mL. Example 2

[0028] An organic flame retardant is prepared by the following steps: 1) Preparation of hybrid matrix Add magnesium chloride, aluminum chloride and rhenium chloride into deionized water, heat to 80°C, stir at a speed of 500r / min for 1h, add mixed alkali solution to adjust pH until pH=11, age for 4h, then heat to 100°C, keep warm for 12h, filter after the reaction, wash the filter cake with anhydrous ethanol and deionized water until the washing liquid is neutral, then vacuum dry for 12h, grind to obtain rhenium ion-doped magnesium aluminum hydrotalcite powder, and control the molar ratio of magnesium chloride, aluminum chloride and rhenium chloride to be 10:5:2; finally prepare rhenium ion-doped magnesium aluminum hydrotalcite powder dispersion: mix rhenium ion-doped magnesium aluminum hydrotalcite powder and deionized water at a mass volume ratio of 1g:1000mL; Add n-hexane to a 2.5 mol / L n-butyl lithium solution, add molybdenum disulfide, heat to 90°C, keep warm for 4 hours, filter, wash the filter cake with n-hexane to obtain product c, add product c to deionized water, ultrasonically peel for 4 hours, add rhenium ion-doped magnesium aluminum hydrotalcite powder dispersion, stir at room temperature for 10 hours, filter after stirring, wash the filter cake with anhydrous ethanol, vacuum dry at 80°C for 10 hours, grind to obtain a hybrid matrix, control the amount ratio of n-hexane, n-butyl lithium solution and molybdenum disulfide to 30mL:10mL:2.0g, and the amount ratio of product c, deionized water and rhenium ion-doped magnesium aluminum hydrotalcite powder dispersion to 1g:1000mL:500mL; 2) Preparation of product a The commercially available flame retardant DOPO (Jiangyin Hanfeng Technology Co., Ltd.) was added to tetrahydrofuran, heated and stirred until dissolved, and p-benzoquinone was added, and then transferred to a microwave oven, heated to 54°C, and the microwave radiation power was controlled to 400W, and the radiation time was 4min. The product was cooled to room temperature, filtered, and washed three times with frozen tetrahydrofuran to obtain a crude product, which was vacuum dried for 10h, and then recrystallized with tetrahydrofuran and dried to obtain product a. The amount ratio of flame retardant DOPO, tetrahydrofuran and p-benzoquinone was controlled to be 100g:400mL:50g; 3) Preparation of product b Add product a to tetrahydrofuran, add isocyanate propyl triethoxysilane and n-butyltin dilaurate in sequence, introduce nitrogen and reflux for 12 hours to obtain product b, and control the amount ratio of product a, isocyanate propyl triethoxysilane and tetrahydrofuran to be 7.4g:6.5g:0.2g:100mL; 4) Preparation of organic flame retardants The prepared hybrid matrix, isocyanate propyl triethoxysilane and n-butyltin dilaurate are added to tetrahydrofuran, the temperature is raised to 55°C, nitrogen is introduced and refluxed for 6 hours. After the reaction is completed, product b is added, deionized water and 1 mol / L hydrochloric acid solution are added, the mixture is kept warm and stirred at a constant speed for 2 hours, and then 30% by weight ammonia water is added, and stirring is continued for 2 hours. The solvent is then removed by rotary evaporation to obtain a crude product, which is added to anhydrous ethanol, filtered, washed, and vacuum dried for 12 hours to obtain an organic flame retardant. The amount ratio of the hybrid matrix, isocyanate propyl triethoxysilane, n-butyltin dilaurate, tetrahydrofuran, product b, deionized water, hydrochloric acid and ammonia water is controlled to be 5g:1g:0.2g:200mL:5g:50mL:3mL:3mL. Example 3

[0029] An organic flame retardant is prepared by the following steps: 1) Preparation of hybrid matrix Add magnesium chloride, aluminum chloride and rhenium chloride into deionized water, heat to 85°C, stir at a speed of 500r / min for 1h, add mixed alkali solution to adjust pH until pH=11, age for 4h, then heat to 100°C, keep warm for 12h, filter after the reaction, wash the filter cake with anhydrous ethanol and deionized water until the washing liquid is neutral, then vacuum dry for 12h, grind to obtain rhenium ion-doped magnesium aluminum hydrotalcite powder, and control the molar ratio of magnesium chloride, aluminum chloride and rhenium chloride to be 10:5:2; finally prepare rhenium ion-doped magnesium aluminum hydrotalcite powder dispersion: mix rhenium ion-doped magnesium aluminum hydrotalcite powder and deionized water at a mass volume ratio of 1g:1000mL; Add n-hexane to a 2.5 mol / L n-butyl lithium solution, add molybdenum disulfide, heat to 90°C, keep warm for 4 hours, filter, wash the filter cake with n-hexane to obtain product c, add product c to deionized water, ultrasonically peel for 4 hours, add rhenium ion-doped magnesium aluminum hydrotalcite powder dispersion, stir at room temperature for 10 hours, filter after stirring, wash the filter cake with anhydrous ethanol, vacuum dry at 85°C for 10 hours, grind to obtain a hybrid matrix, control the amount ratio of n-hexane, n-butyl lithium solution and molybdenum disulfide to 35mL:10mL:3g, and the amount ratio of product c, deionized water and rhenium ion-doped magnesium aluminum hydrotalcite powder dispersion to 1g:1000mL:1000mL; 2) Preparation of product a The commercially available flame retardant DOPO (Jiangyin Hanfeng Technology Co., Ltd.) was added to tetrahydrofuran, heated and stirred until dissolved, p-benzoquinone was added, and then transferred to a microwave oven, heated to 55°C, and the microwave radiation power was controlled to 500W, the radiation time was 3min, cooled to room temperature, filtered, and washed three times with frozen tetrahydrofuran to obtain a crude product, which was vacuum dried for 10h, then recrystallized with tetrahydrofuran, and dried to obtain product a, and the amount ratio of flame retardant DOPO, tetrahydrofuran and p-benzoquinone was controlled to be 100g:500mL:50g; 3) Preparation of product b Add product a to tetrahydrofuran, add isocyanate propyl triethoxysilane and n-butyltin dilaurate in sequence, introduce nitrogen and reflux for 12 hours to obtain product b, and control the amount ratio of product a, isocyanate propyl triethoxysilane and tetrahydrofuran to be 7.5g:6.5g:0.2g:100mL; 4) Preparation of organic flame retardants The prepared hybrid matrix, isocyanate propyl triethoxysilane and n-butyltin dilaurate are added to tetrahydrofuran, the temperature is raised to 65°C, nitrogen is introduced and refluxed for 3 hours. After the reaction is completed, product b is added, deionized water and 1 mol / L hydrochloric acid solution are added, the mixture is kept warm and stirred at a constant speed for 2 hours, and then 30% by weight ammonia water is added, and stirring is continued for 2 hours. The solvent is then removed by rotary evaporation to obtain a crude product, which is added to anhydrous ethanol, filtered, washed, and vacuum dried for 12 hours to obtain an organic flame retardant. The amount ratio of the hybrid matrix, isocyanate propyl triethoxysilane, n-butyltin dilaurate, tetrahydrofuran, product b, deionized water, hydrochloric acid and ammonia water is controlled to be 6g:1g:0.1g:300mL:5g:100mL:5mL:5mL. Example 4

[0030] A PVC black masterbatch, comprising the following raw materials in parts by weight: 30 parts of acrylonitrile-butadiene-styrene copolymer, 70 parts of carbon black, 10 parts of the organic flame retardant prepared in Example 1, 5 parts of polyethylene wax, and 2 parts of talc; The carbon black is ground and sieved for later use; styrene-butadiene-acrylonitrile copolymer is added into a mixer, the temperature is raised to 200°C, and the mixture is mixed for 1 hour, and then polyethylene wax is added. After mixing for 30 minutes, carbon black, talcum powder and organic flame retardant are added, and the black masterbatch is obtained after mixing for 2 hours. Example 5

[0031] A PVC black masterbatch, comprising the following raw materials in parts by weight: 40 parts of polystyrene, 80 parts of carbon black, 15 parts of the organic flame retardant prepared in Example 2, 8 parts of polyethylene wax, and 4 parts of talc; The carbon black is ground and sieved for later use; polystyrene is added into a mixer, the temperature is raised to 200°C, and the mixer is mixed for 1.2 hours, and then polyethylene wax is added. After mixing for 30 minutes, carbon black, talcum powder and organic flame retardant are added, and the black masterbatch is obtained after mixing for 2 hours. Example 6

[0032] A PVC black masterbatch, comprising the following raw materials in parts by weight: 50 parts of styrene-butadiene copolymer, 90 parts of carbon black, 25 parts of the organic flame retardant prepared in Example 3, 10 parts of sodium stearate, and 5 parts of talc; The carbon black is ground and sieved for later use; the styrene-butadiene copolymer is added into a mixer, the temperature is raised to 200°C, and the mixer is mixed for 1.5 hours, and then sodium stearate is added. After mixing for 30 minutes, the carbon black, talcum powder and organic flame retardant are added, and the black masterbatch is obtained after mixing for 2 hours.

[0033] Comparative Example 1

[0034] Compared with Example 4, this comparative example uses the hybrid matrix prepared in step 1) of Example 1 as a flame retardant instead of the organic flame retardant in Example 4.

[0035] Comparative Example 2

[0036] Compared with Example 4, this comparative example uses a commercially available flame retardant DOPO (Jiangyin Hanfeng Technology Co., Ltd.) to directly replace the organic flame retardant prepared in Example 4.

[0037] The coloring effect and flame retardant performance of the masterbatches prepared in Examples 4-6 and Comparative Examples 1-2 were tested, and the results are shown in Table 1 below: Table 1

[0038] It can be seen from Table 1 above that the masterbatches prepared in Examples 4-6 have uniform color and excellent flame retardant properties, wherein the coloring effect of the masterbatch is tested in accordance with standard QB / T 2894-2007, the flame retardant grade is tested in accordance with standard UL-94, and the oxygen index is tested in accordance with standard GB / T 2406.3-2022.

[0039] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing an organic flame retardant, characterized in that: The preparation steps include the following: Step 1): Preparation of product a: add flame retardant DOPO to tetrahydrofuran, heat and stir until dissolved, add p-benzoquinone, carry out microwave heating reaction, cool to room temperature after the reaction is completed, filter, wash with ice-crystallized tetrahydrofuran to obtain a crude product, vacuum dry, recrystallize with tetrahydrofuran, and dry to obtain product a; Step 2): Preparation of product b: Add product a to tetrahydrofuran, and add isocyanatepropyltriethoxysilane and n-butyltin dilaurate in sequence, introduce nitrogen gas for reflux reaction, and obtain product b; Step 3): Preparation of organic flame retardant: Add the hybrid matrix, isocyanate propyl triethoxysilane and n-butyltin dilaurate into tetrahydrofuran, heat up, introduce nitrogen for reflux reaction, add the product b obtained in step 2) after the reaction is completed, add deionized water and hydrochloric acid solution, keep warm and stir evenly, add ammonia water, continue stirring and react, and then rotary evaporate to obtain a crude product, add it into anhydrous ethanol, filter, wash, and vacuum dry to obtain an organic flame retardant.

2. The preparation method according to claim 1, characterized in that: In step 1), the amount ratio of the flame retardant DOPO, tetrahydrofuran and p-benzoquinone is 100g: (300-500)mL: 50g; the microwave heating reaction has a heating temperature of 50-55°C, a microwave power of 300-500W, and a reaction time of 3-5min.

3. The preparation method according to claim 1, characterized in that: In step 2), the usage ratio of the product a, isocyanatepropyltriethoxysilane, n-butyltin dilaurate and tetrahydrofuran is (7.2-7.5) g: 6.5 g: (0.1-0.2) g: 100 mL.

4. The preparation method according to claim 1, characterized in that: In step 3), the amount ratio of the hybrid matrix, isocyanatepropyltriethoxysilane, n-butyltin dilaurate, tetrahydrofuran, product b, deionized water, hydrochloric acid solution and ammonia water is (5-6) g: 1 g: (0.1-0.2) g: (100-300) mL: 5 g: (10-100) mL: (1-5) mL: (1-5) mL; the heating temperature is 55-65° C., and the reflux reaction time is 3-6 h; the concentration of the hydrochloric acid solution is 0.5-1 mol / L; and the mass percentage of the ammonia water is 25-30%.

5. The preparation method according to claim 4, characterized in that: The hybrid matrix is ​​prepared by the following steps: Step 1): Add magnesium chloride, aluminum chloride and rhenium chloride into deionized water, stir evenly after heating, add mixed alkali solution to adjust pH, heat and react after aging, filter after the reaction, wash the filter cake with anhydrous ethanol and deionized water until the washing liquid is neutral, then vacuum dry and grind to obtain rhenium ion-doped magnesium aluminum hydrotalcite powder, and prepare rhenium ion-doped magnesium aluminum hydrotalcite powder dispersion; Step 2): Add n-hexane to n-butyl lithium solution, add molybdenum disulfide, heat and then carry out heat preservation reaction, filter, wash the filter cake with n-hexane to obtain product c, add product c into deionized water, ultrasonically peel, add rhenium ion-doped magnesium aluminum hydrotalcite powder dispersion, stir at a uniform speed at room temperature, filter after stirring, wash the filter cake with anhydrous ethanol, vacuum dry, grind, and obtain a hybrid matrix.

6. The preparation method according to claim 5, characterized in that: The molar ratio of the magnesium chloride, aluminum chloride and rhenium chloride is 10:5:(1-2); the mixed alkali solution is prepared by the following steps: a sodium carbonate solution with a concentration of 3 g / mL and a sodium hydroxide solution with a concentration of 5 g / mL are stirred evenly in a volume ratio of 1:1 to prepare a mixed alkali solution; the rhenium ion-doped magnesium-aluminum hydrotalcite powder dispersion is prepared by the following steps: rhenium ion-doped magnesium-aluminum hydrotalcite powder and deionized water are mixed in a mass volume ratio of 1 g:1000 mL.

7. The preparation method according to claim 5, characterized in that: The dosage ratio of n-hexane, n-butyl lithium solution and molybdenum disulfide is (30-35) mL: 10 mL: (1.5-3) g, and the dosage ratio of the product c, deionized water and rhenium ion-doped magnesium aluminum hydrotalcite powder dispersion is 1 g: 1000 mL: (500-1000) mL.

8. Use of an organic flame retardant prepared by the method according to any one of claims 1 to 7 in PVC black masterbatch, characterized in that: The PVC black masterbatch comprises, by weight, 10 to 25 parts of an organic flame retardant, 30 to 50 parts of a carrier, 70 to 90 parts of carbon black, 5 to 10 parts of a dispersant and 2 to 5 parts of talc.

9. The use according to claim 8, characterized in that: The PVC black masterbatch is prepared by the following method: grinding and sieving carbon black for later use, adding a carrier into a mixer, heating to 190-200° C. and mixing for 1-2 hours, then adding a dispersant, continuing mixing for 30-45 minutes, adding carbon black, talcum powder and an organic flame retardant, and continuing mixing for 1-3 hours to obtain a black masterbatch.

10. The use according to claim 9, characterized in that: The carrier is one or more of styrene-butadiene-acrylonitrile copolymer, polystyrene and styrene-butadiene copolymer mixed in any proportion, and the dispersant is polyethylene wax or stearic acid metal salt.

Citation Information

Patent Citations

  • Environment-friendly PVC black master batch

    CN107118470A

  • Attapulgite / hydrotalcite compound flame retardant material and preparation method thereof

    CN102408581A

  • Supported Co-MoS2 / LDHS hydro-refining catalyst and application thereof

    CN106268871A

  • Hydrotalcite-like compound as well as preparation method and application thereof

    CN106957453A

  • Molybdenum disulfide intercalated hydrotalcite composite material and preparation method and application thereof

    CN107774283A